Ailing of AIDS and unaided: a critical-historical review of HIV testing and "spaces" of disclosure for Catholic clerics and religious in South Africa during the 1990s - Joshua, Stephen M. (Faculty of the Humanities, University of the Free State, 2016)
As was the case with the larger South African society during the 1990s, the Catholic Church was not without error in the manner in which it dealt with HIV and AIDS. Whereas the church was involved in activism for the rights of People Living with HIV and AIDS (PLWHA) on the outside, it ironically ignored, arguably even muted, voices of PLWHA within its inner ranks, especially the priests, religious, and candidates for spiritual formation and vocation at the seminaries. Sadly, HIV testing is intricately connected to the disclosure of HIV positive status for Catholic clerics and religious on account of the vow to celibacy. An HIV positive test result presents both a health and a moral dilemma for the church. So sensitive was the issue that the Southern Africa Catholic Bishops’ Conference debated on it in the entire 1990s, and abandoned it inconclusively. Meanwhile, HIV positive priests agonised in silence and the religious in convents would only confess their status on death beds due to foreseen hostilities by their peers and superiors. Based on oral interviews and archival materials, such as correspondence letters and minutes, the article is a critical-historical review of how the Catholic Church handled HIV testing and disclosure within its inner ranks during the 1990s. It is argued that, as was the case of condom use in HIV prevention, the Catholic Church struggled throughout the 1990s to accept that priesthood and religious life was not immune to the social challenge of HIV and AIDS and thereby failed to accept and care for HIV positive priests and religious.
Keywords: HIV testing and disclosure; AIDS; Religious; Priests; South Africa; Catholic church; Care; Stigma